2014
DOI: 10.1364/josab.31.001308
|View full text |Cite
|
Sign up to set email alerts
|

Raman random laser in one-dimensional system

Abstract: The probability of occurrence of random cavities' resonance frequency in the Stokes bandwidth of the Raman active medium can cause Raman laser oscillation in the random structures. Due to the small bandwidth of Raman line shape, the probability of the simultaneous appearance of random cavity resonance frequencies in the cascade Stokes line shapes is small. As a result, the cascade Raman laser oscillation effects on the saturation behavior are negligible. The nonlinear transmission matrix method is employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The probability of the Raman random lasing, effects of disordered parameter on it, spatial power distribution, light localization, and the threshold pump power were thoroughly studied by calculating the statistical behavior, and results were in agreement with experimental results [29]. In the present study, using this method, we demonstrated numerically the possibility of selecting any desired modes out of the available quasi-modes (QMs).…”
supporting
confidence: 70%
See 4 more Smart Citations
“…The probability of the Raman random lasing, effects of disordered parameter on it, spatial power distribution, light localization, and the threshold pump power were thoroughly studied by calculating the statistical behavior, and results were in agreement with experimental results [29]. In the present study, using this method, we demonstrated numerically the possibility of selecting any desired modes out of the available quasi-modes (QMs).…”
supporting
confidence: 70%
“…In the present study, using this method, we demonstrated numerically the possibility of selecting any desired modes out of the available quasi-modes (QMs). Our method is based on the TMM as well as solving the differential equations of Raman Stokes amplification [29]. The TMM is a frequency domain method that is widely used for study of the random lasing [5,6,11,15,16].…”
mentioning
confidence: 99%
See 3 more Smart Citations